Preventive maintenance for effective operation of boilers in Kuwait industry - Azemi, Ahmed S KH R Q (Kulliyyah of Engineering, International Islamic University Malaysia, 2022)
There have been several studies on heat transfer surfaces, where air and water temperatures are elevated by the heat transfer from other media. This research presented a new approach which entails a preventive maintenance technique, for improving the boiler efficiency, analysed using a specific methodology and literature data. A high boiler efficiency can be achieved, using an optimal approach of the preventive method, with an optimisation technique. Particularly in the State of Kuwait, steam boilers used to be more in numbers, and in some industries, breakdown and failures during the operation have been found. Therefore, in these cases, some additional care is required on such studies; a preventive maintenance technique is a suitable approach for the boilers used in the oil and gas industries in Kuwait. This approach has numerous advantages that make this technique helpful for any plant size. Most of the oil and gas industries in Kuwait are significant, and this approach will be cost-effective and efficient for large industries. When the plant assets value is high, the return will be high, and while using this approach, the proper maintenance helps to keep the high boiler performance, even for the old system. The results obtained showed that, the preventive maintenance is essential not only for improving the production rate of the industry, it also helps to make the boilers safe for the operators to work there. Based on the analysis conducted, it was revealed that, the preventive maintenance reduces the operating costs by preventing boiler failures. The research further recommended that, the results produced in the present thesis proved the benefits of the preventive maintenance for a high boiler efficiency in oil and gas industries in the State of Kuwait.